2015
DOI: 10.1016/j.snb.2015.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Dually responsive one dimensional photonic crystals with reversible color changes

Abstract: We developed a smart and reproducible fabrication of pH/temperature dually responsive sensor by taking advantage of one dimensional photonic crystals (1DPCs). TiO 2 /P(AA-bis-NiPAAm) 1DPCs were fabricated by spin-coating TiO 2 and copolymers P(AA-bis-NiPAAm) onto silicon wafers. When using the 1DPCs dually responsive polymer films as pH/temperature sensor, both refraction wavelength and peak refraction intensity values were derived, and the reproducible change could be observed by the naked eye through a chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
(49 reference statements)
0
23
0
Order By: Relevance
“…45 To reduce the number of layers required to get a sufficient reflection band, the refractive index contrast between the layers was enhanced by intercalating inorganic layers or doping polymer layers with inorganic particles, such as TiO 2 or ZrO 2 . 46,47 Besides a less labour intensive process, doping with inorganic particles also provides a way for the fabrication of all-gel Bragg reflectors consisting of PNIPAM and PNIPAM doped with inorganic particles. All-gel Bragg reflectors might be desirable for the mechanical properties as well as the speed of mass transport of large polar molecules for chemical or biological sensing applications compared to the use of brittle and hydrophobic non-hydrogel polymers, such as poly(para-methyl-styrene).…”
Section: Two-way Temperature Responsive Photonic Polymersmentioning
confidence: 99%
“…45 To reduce the number of layers required to get a sufficient reflection band, the refractive index contrast between the layers was enhanced by intercalating inorganic layers or doping polymer layers with inorganic particles, such as TiO 2 or ZrO 2 . 46,47 Besides a less labour intensive process, doping with inorganic particles also provides a way for the fabrication of all-gel Bragg reflectors consisting of PNIPAM and PNIPAM doped with inorganic particles. All-gel Bragg reflectors might be desirable for the mechanical properties as well as the speed of mass transport of large polar molecules for chemical or biological sensing applications compared to the use of brittle and hydrophobic non-hydrogel polymers, such as poly(para-methyl-styrene).…”
Section: Two-way Temperature Responsive Photonic Polymersmentioning
confidence: 99%
“…It was also observed that the original swelling behaviour in response to the pH of the SH‐0 hydrogel was converted completely with the addition of silicon monomer. PHEMA and PVP were both responsive to acidic conditions; however, the silicone hydrogels were more responsive to basic conditions than acidic conditions.…”
Section: Resultsmentioning
confidence: 94%
“…Liu et al developed a reproducible pH/temperature dually responsive sensor which could distinguish between different solvents by a change in colour. The sensors were prepared using one‐dimensional photonic crystals which were fabricated by coating silicon wafers with TiO 2 nanoparticles and the copolymer poly(acrylic acid‐bis‐ N ‐isopropylacrylamide) . Guenther et al developed a piezoresistive sensor which used a hydrogel as the chip for detecting target solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The Bragg stacks approach has also been used to prepare P(NIPAM‐ co ‐AA)‐based photonic structures. The concept has been employed to prepare a multilayer system by alternatively spin‐coating of NIPAM–AA polymer precursor and TiO 2 layer as a high‐refractive‐index component . The multilayer system is baked at higher temperature resulting in 1D photonic stacks that change the structural color of the system by changing temperature and at different pH values.…”
Section: Artificial Materialsmentioning
confidence: 99%